A multi-method exploratory study of stress, coping, and substance use among high school youth in private schools - Leonard, Noelle R.; Gwadz, Marya V.; Ritchie, Amanda; Linick, Jessica L.; Cleland, Charles M.; Elliott, Luther; Grethel, Michele (Frontiers in Psychology, 2015)
There is growing awareness that students’ experiences of stress may impede academic success, compromise mental health, and promote substance use. We examined these factors in an under-studied population, private/independent high school students, using a multi-method and iterative data collection and analytic process. We first conducted qualitative interviews with faculty and staff at a number of highly competitive private schools, followed by an anonymous survey with 128 eleventh-grade students from two of these settings, and then conducted a qualitative exploration of the quantitative results with a subset of students. Next, a set of Expert Panel members participated in qualitative interviews to reflect on and interpret study findings. Overall, we found students experienced high levels of chronic stress, particularly in relation to academic performance and the college admissions process. While students described a range of effective, adaptive coping strategies, they also commonly internalized these serious pressures and turned to alcohol and drugs to cope with chronic stress, although not typically at problematic levels. We discuss study implications for both schools and families derived from the Expert Panel.